Recenze a anotace 1_2009 (Romano džaniben, 2009)
Ceija Stojka / Meine Wahl zu schreiben – ich kann es nichtPeter Stojka, Rastislav Pivoň / Náš život – Amáro TrajoLumini,ta Mihai Cioabˇa / Lacrimi Rome / Romane asvaCtibor Nečas / Špalíček romských miniaturKarol Janas / Zabudnuté táboryKathrin Janka (ed.) / Geraubte LebenAdam Bartosz / Katalog zbiorów cyganologicznych Muzeum okregowego w Tarnowie /Catalogue of The Romany Collections at the District museum in TarnówMałgorzata Mirga-Tas, Boguslawa Delimata, Krzysztof Gil / Romani ArtValentina Glajar a Domnica Radulescu (eds.) / „Gypsies“ in European Literature and Culture